2020
DOI: 10.3390/bdcc4020012
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized Heritage-Oriented Recommender System Based on Extended Cultural Tourist Typologies

Abstract: Recent developments in digital technologies regarding the cultural heritage domain have driven technological trends in comfortable and convenient traveling, by offering interactive and personalized user experiences. The emergence of big data analytics, recommendation systems and personalization techniques have created a smart research field, augmenting cultural heritage visitor’s experience. In this work, a novel, hybrid recommender system for cultural places is proposed, that combines user preference with cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Therefore, the basic function of the CHATS personalization module is the definition of the user's requirements and characteristics by defining his profile. Most similar surveys have used the questionnaire to categorize users according to their answers [39,40,9,41]. Viewing a small questionnaire with simple but targeted questions about the user's profile and interests at the beginning of the CHATS application is a common and effective method in corresponding cases of personalized information to gather the necessary information about the user profile.…”
Section: Personalization Modulementioning
confidence: 99%
“…Therefore, the basic function of the CHATS personalization module is the definition of the user's requirements and characteristics by defining his profile. Most similar surveys have used the questionnaire to categorize users according to their answers [39,40,9,41]. Viewing a small questionnaire with simple but targeted questions about the user's profile and interests at the beginning of the CHATS application is a common and effective method in corresponding cases of personalized information to gather the necessary information about the user profile.…”
Section: Personalization Modulementioning
confidence: 99%
“…Ross [25]'s study on Alentejo in Portugal showed that more personalized individual-based guiding activities can be used in co-creating experiences by cultural tourism providers to deliver more meaningful experiences also appealing to visitors with alternative sets of beliefs and motivations. Konstantakis et al [26]'s work demonstrated that it is possible to provide higher quality and more relevant cultural recommendations when including information regarding the cultural background of tourists. In the context of audio tours, Shilov et al [27] proposed automatically generated personalized audio tours based on the context and tourists' preferences.…”
Section: Personalization In Tourismmentioning
confidence: 99%
“…The most recent CUX studies [3][4][5][6][7][8] show that users of applications and services of cultural content tend to carry their own cultural characteristics and preferences when visiting destinations of cultural interest, learn and interact differently with cultural content, thus obtaining a virtually unique cultural experience. To cope with this tendency, cultural spaces need to search for novel ways of providing more personalised experiences to their visitors [4,9,10]. To that end, various research efforts have been made to identify different profiles of cultural visitors based on their background and preferences, and classify them into distinct visitor types [9,[11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…To cope with this tendency, cultural spaces need to search for novel ways of providing more personalised experiences to their visitors [4,9,10]. To that end, various research efforts have been made to identify different profiles of cultural visitors based on their background and preferences, and classify them into distinct visitor types [9,[11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%